The effects of store atmosphere attributes on store loyalty intentions of hypermarket/supermarket customers - Yalçın, Müge; Kocamaz, Tuncay (İktisadi ve İdari Bilimler Dergisi, 2003)
Increasing competition in Turkish grocery market is pushing retailers to search for ... attributes and store loyalty intentions of the customers are linked.